Crystal Structures and Catalytic Mechanism of l‐erythro‐3, 5‐Diaminohexanoate Dehydrogenase and Rational Engineering for Asymmetric Synthesis of β‐Amino Acids. Issue 18 (24th March 2021) - Liu, Na; Wu, Lian; Feng, Jinhui; Sheng, Xiang; Li, Jian; Chen, Xi; Li, Jianjiong; Liu, Weidong; Zhou, Jiahai; Wu, Qiaqing; Zhu, Dunming
Abstract: Amino acid dehydrogenases (AADHs) have shown considerable potential as biocatalysts in the asymmetric synthesis of chiral amino acids. However, compared to the widely studied α‐AADHs, limited knowledge is available about β‐AADHs that enable the synthesis of β‐amino acids. Herein, we report the crystal structures of a l ‐ erythro ‐3, 5‐diaminohexanoate dehydrogenase and its variants, the only known member of β‐AADH family. Crystal structure analysis, site‐directed mutagenesis studies and quantum chemical calculations revealed the differences in the substrate binding and catalytic mechanism from α‐AADHs. A number of rationally engineered variants were then obtained with improved activity (by 110–800 times) toward various aliphatic β‐amino acids without an enantioselectivity trade‐off. Two β‐amino acids were prepared by using the outstanding variants with excellent enantioselectivity (>99 % ee ) and high isolated yields (86–87 %). These results provide important insights into the molecular mechanism of 3, 5‐DAHDH, and establish a solid foundation for further design of β‐AADHs for the asymmetric synthesis of β‐amino acids. Abstract : The substrate binding and catalytic mechanism of l ‐ erythro ‐3, 5‐diaminohexanoate dehydrogenase, the only known member of the β‐amino acid dehydrogenase family, are shown to be quite different from those of its α‐counterparts. Subsequent rational engineering expanded the substrate scope without reducing the enantioselectivity, enabling efficient asymmetric synthesis of β‐amino acids.